SELF-EFFICACY DAN SELF REGULATED LEARNING TERHADAP PEMBELAJARAN MATEMATIKA: SYSTEMATIC LITERATURE REVIEW DENGAN PENDEKATAN PRISMA - Kusuma, Arum; Pujiastuti, Heni; Anriani, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning at the secondary school level still faces challenges related to students’ low achievement caused by a lack of self-confidence and independent learning management skills. This study examines the influence of both variables on mathematics learning among junior and senior high school students through a Systematic Literature Review (SLR) using the PRISMA 2020 approach. Data were collected from the Consensus and Google Scholar databases using relevant keywords, resulting in 78 articles. After the screening, eligibility, and selection stages, 11 articles met the inclusion criteria. The synthesis findings indicate that self-efficacy and self-regulated learning (SRL) have a significant effect on mathematics learning. Self-efficacy enhances students’ motivation and resilience in dealing with difficult tasks, while SRL supports independent learning through planning, monitoring, and evaluation processes. This study concludes that strengthening both variables is an effective strategy for improving mathematics learning at the secondary education level.